Low-dose Bisphenol-A regulates inflammatory cytokines through GPR30 in mammary adipose cells. (November 2019) - Cimmino, Ilaria; Oriente, Francesco; D'Esposito, Vittoria; Liguoro, Domenico; Liguoro, Pasquale; Ambrosio, Maria Rosaria; Cabaro, Serena; D'Andrea, Francesco; Beguinot, Francesco; Formisano, Pietro; Valentino, Rossella
Abstract : The dramatic rise in obesity and metabolic syndrome can be related, at least in part, to environmental chemical factors such as Bisphenol-A (BPA). In this study, we aimed to understand the effects of low-dose Bisphenol-A on the human mature adipocytes and stromal vascular fraction (SVF) cells, obtained from subcutaneous mammary adipose tissue of overweight female patients, undergoing surgical mammary reduction. 24 and/or 48-h exposure to BPA 0.1 nM elicited significant increase of the inflammatory molecules interleukin-6 (IL-6), interleukin-8 (IL-8), monocyte chemo-attractant protein 1α (MCP1α) and induced G protein-coupled estrogen receptor 30 (GPR30) levels more than two-fold both in mature adipocytes and SVF cells. These effects were similar to that obtained in the presence of GPR30-specific agonist G1 (100 nM) and were reverted by G15 (1 µM), a GPR30-selective antagonist. As a result of BPA-GPR30 signaling activation, fatty acid synthase (FAS) and leptin mRNA levels were significantly higher upon BPA exposure ( P < 0.05) in mature adipocytes, with an opposite effect on adiponectin (ADIPOQ). In addition, an increase in SVF cell proliferation and ERK1/2 phosphorylation, was observed, compared to untreated cells. G15 reverted all of these effects. Interestingly, the action of BPA on SVF cell growth was mimicked by IL-8 treatment and was reverted by incubation with anti-IL8 antibodies. All these data suggest that BPA at 0.1 nM, a ten times lower concentration than environmental exposure, increases the expression of pro-inflammatory cytokines via GPR30 both in mature mammary adipocytes and in SVF cells with a possible involvement of IL-8.